Microwave Soil Heating Promotes Strawberry Runner Production and Progeny Performance - Graham Ian Brodie; Dylan John McFarlane; Muhammed Jamal Khan; Valerie Buu Giao Phung; Scott William Mattner (Energies, 2022)
Strawberry runners (transplants) in many regions of the world are produced in soils treated with chemical fumigants to control pathogens and weeds and meet phytosanitary requirements. Many fumigants, however, are under threat of withdrawal because of concerns over their impact on the environment (e.g., methyl bromide). The current study considered the use of microwaves for heat disinfestation of soil for field-grown runners for the first time. Results from two field experiments showed that microwave treatment reduced the survival of buried inoculum of the strawberry pathogens Fusarium oxysporum (by up to 93%) and Sclerotium rolfsii (by up to 100%) compared with untreated soil. Furthermore, the treatment reduced the subsequent growth of these pathogens in the laboratory by up to 82% and 100%, respectively. Microwave treatment also reduced the natural DNA concentration of Pythium spp. (clades I & F) in soil by up to 94% compared with untreated soil. The effect of microwave against soilborne pathogens reduced as soil depth increased. Microwave treatment reduced the emergence of weeds in field soils by up to 65% and increased runner yields by 10–37%. The effect of microwave treatment on runner yield was greater when all soil was treated, rather than when strips of soil around the mother plants were treated. Results from complimentary pot experiments showed that early strawberry growth in the glasshouse was equivalent in soils treated with microwave or the fumigant methyl bromide/chloropicrin. Furthermore, the early performance of runners sourced from field soils treated with microwave or methyl bromide/chloropicrin was equivalent. Results from the pot experiments also showed that steam treatment required 10 times more energy per mass of soil to disinfest than microwave. The limitations of microwave in the current experiments are discussed, but the capacity for the technology to disinfest field soils in an energy-efficient manner demonstrates its potential for further development as an alternative to soil disinfestation with chemical fumigants.